2019
DOI: 10.1007/s00268-019-05129-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Ice Packs Reduce Postoperative Midline Incision Pain, NSAID or Narcotic Use?

Abstract: Background Adequate postoperative analgesia, especially after major abdominal surgery is important for recovery, early mobility, and patient satisfaction. We aimed to study the effects of cryotherapy via an ice pack in the immediate postoperative period, for patients undergoing major abdominal operations. Methods This prospective study was conducted at our tertiary care referral center in a low-middle-income country setting. The preoperative patient characteristics, intra-operative variables, and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…After cold pack removal, pain reduction effect lasted for 24 h postoperatively. In parallel, the study of Watkins et al 19 and later study of Ravindhran et al 20 concluded that significant pain reduction and morphine consumption are decreased after open abdominal surgery until postoperative day 3 using 24‐h ice pack compression. The study of Zencir et al 22 applied cold pack on to open heart surgical sites for 20 min.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…After cold pack removal, pain reduction effect lasted for 24 h postoperatively. In parallel, the study of Watkins et al 19 and later study of Ravindhran et al 20 concluded that significant pain reduction and morphine consumption are decreased after open abdominal surgery until postoperative day 3 using 24‐h ice pack compression. The study of Zencir et al 22 applied cold pack on to open heart surgical sites for 20 min.…”
Section: Discussionmentioning
confidence: 94%
“…There are many theories explaining the mechanisms of cold‐reducing pain mainly involving pro‐inflammatory cytokines suppression and delaying conduction velocity of peripheral nerves. It is proved to be effective in gynecologic surgery, 8,10–12 maxillofacial surgery, 13–14 orthopedic surgery, 15–17 general surgery, 3,18–21 and open heart surgery 22 …”
Section: Discussionmentioning
confidence: 99%
“…The overall results revealed beneficial outcomes in terms of pain reduction and pain management. [8][9][10][11] The present study is the first to emphasize the effects of cryotherapy or cold application in ESWL treatment. In addition, this study used the change of maximum VAS score from baseline for the primary outcome instead of the patient's stated VAS score after he or she had his/her operation.…”
Section: Original Article Smjmentioning
confidence: 99%
“…6,7 Many studies have been published in regard to cryotherapy for pain reduction, for example with knee operations, thoracic operations, gynecologic operations, and abdominal operations. [8][9][10][11] However, no previous study has reported the analgesic effect of cryotherapy on ESWL. The aim of this study was to evaluate the effectiveness of cryotherapy regarding pain control during ESWL for urolithiasis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cryotherapy was a simple, easy applied, effective, noninvasive and safe with low cost nursing intervention to relieve pain. It provided analgesic effect, increase the threshold of pain, enhance patient's autonomy and cooperation and is free from undesirable effects (Hawk, 2017, Ravindhran et al, 2019Tareq et al, 2020). Sandhya and Jebarose (2020) in a study entitled "Effectiveness of Ice Compress Application upon the Level of Pain among Patients with Chest Drainage" concluded that application of ice pack is effective in pain relief and achieving comfort with undesirable effects.…”
Section: Mcgee Et Al (2019)mentioning
confidence: 99%